Construction and improvement strategies of an age-friendly evaluation system for public spaces in affordable housing communities: a case study of Shenzhen - Jiwen Han; Jiwen Han; Hang Ma; Mohan Wang; Jinqi Li (Frontiers Media S.A., 2024)
Characterized by early construction periods, as the concentration of low-income populations and a high level of aging, affordable housing communities face prominent challenges such as incongruence between age-friendly construction and the needs of the older adult population. It is urgent to provide pathways and tools for identifying age-friendly issues and optimizing the built environment. The systematic evaluation of age-friendly communities serves as the foundation for implementing intervention measures by developers. Therefore, the construction of a scientifically systematic evaluation system becomes an objective necessity for age-friendly community development. Building upon existing research, this study systematically outlines the subjects, processes, methods, and content involved in constructing an age-friendly community evaluation system. By the methods such as factor analysis and analytical hierarchy process (AHP), the study focuses on the public spaces of affordable housing communities in Shenzhen as a case for constructing an age-friendly evaluation system. The empirical validation of the indicator system is conducted, and the application results are resulted into concrete improvement recommendations and action items, aiming to provide a practical, quantitative tool for community age-friendliness evaluation. The study reveals that adhering to an effective evaluation process, exploring collaborations among multiple stakeholders, determining hierarchical evaluation criteria, and adopting diversified evaluation methods are key to constructing an age-friendly evaluation system for communities. Additionally, the specificity of the evaluation system is influenced by regional demographic structures, policy backgrounds, and the built environment.